Avortement, dépénalisation et droit à la vie du fœtus : le cas coréen au prisme de l’exemple japonais - Isabelle Konuma (Tracés, 2017)
The Constitutional Court of Korea declared in conformity with the Constitution a provision of the penal code condemning abortion carried out by a doctor or assimilated. It is in this context that Yang Hyunah chooses to shed light on the rule of law and practice of abortion, building her demonstration around the voice of women. In this article we analyze Yang’s article in a comparative logic with the eugenic regime and the penalization of abortion in Japan, as well as with the development of feminist movements and the disabled movements.